Anthropology of Islamic Law as an Approach in the Practice of Buying and Selling Online - Doli Witro; Zufriani; Tajul Arifin; Mohamad Athoillah (Fakultas Syariah IAIN Kediri, 2022)
Information technology has changed the ways of transacting and opened up new opportunities in conducting business transactions. An online sale and purchase agreement via the internet is considered valid if it meets subjective and objective conditions. Trading business activities via the internet are known as electronic commerce (e-commerce). It has become a necessity that society always experiences changes which are often followed by changes in mindset and values. On the other hand, the legal anthropology approach in research on Islamic law, both the study of normative laws (in the Qur’an) and empirical ones (in the practice of Muslims), has not been fully used. This article describes the anthropological approach of Islamic law in viewing the phenomenon of online buying and selling practices in Indonesia. This article aims to highlight the practice of buying and selling online using an anthropological approach to Islamic law. This article is qualitative research with library research. This article uses a Normative-Anthropological approach. The data in this study were obtained from library materials such as books, journals, and others related to the problems studied, namely the anthropology of Islamic law and online buying and selling. Data analysis techniques used are data condensation, data presentation, and drawing conclusions. The analysis results show that economic activity, including buying and selling online, relies heavily on language as a symbol of interaction. In other words, humans and the economy always prioritize symbolic interactionism in negotiating the desires and expectations of sellers and buyers, that is where anthropology and economics meet.